Drugs and contemporary warfare - Kan, Paul Rexton (Potomac Books, 2009)
Hazy shades of war -- Drugging the battlefield : drugs as war funding -- High at war : drug use by combatants -- Narcotics and nation-building : drug trade as post-conflict complication -- Sober lessons for the future: the dynamics of drug-fueled conflicts -- Shaky paths forward : strategies and approaches in drug-fueled conflicts